Designing the new European Union - Berger, Helge; Moutos, Thomas (Contributions to economic analysis, 2007)
This volume is based on papers delivered at the second CESifo-Delphi Conferences (Munich, November 2003, and Delphi, June 2004), which are jointly organized by CESifo and the Department of International and European Economic Studies of the Athens University of Economics and Business. The CESifo-Delphi Conferences are organized every two years and involve a two-stage process. Following an initial call for abstracts, a number of authors were selected and invited to present their papers at a workshop meeting in Munich. After further refereeing, some of the authors were invited to present (possibly revised) versions of their papers at the final conference meeting in Delphi. Contributions to Economic Analysis was established in 1952. The series purpose is to stimulate the international exchange of scientific information. The series includes books from all areas of macroeconomics and microeconomics.